1975
DOI: 10.1902/jop.1975.46.8.469
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties of Periodontal Dressings

Abstract: The relationship between the build-up of bacterial plaque at the dento-gingival junction and the development of gingivitis is well established. The susceptibility of patients requiring periodontal surgery to the pathogenic potential of plaque would seem to necessitate the protection of the surgically treated area by a periodontal dressing until adequate plaque control by the patient is possible. In the light of clinical experience, an investigation was undertaken into the antibacterial properties of certain pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Eugenol has been shown to have antibacterial properties in several studies in vitro (Linghorne & O'Connell 1949, CoU man 1962, Persson & Thilander 1968a, O'Neil 1975, Haugen et al 1977; in vivo, it has been noted that plaque composition is definitely altered, presumably as a result of selective inhibition (Coppes et al-1967, Heaney et al 1972. Pihlstrom et al (1977) considered that the total number of microorganisms was not noticeably reduced by eugenol.…”
Section: Therapeutic Effectsmentioning
confidence: 99%
“…Eugenol has been shown to have antibacterial properties in several studies in vitro (Linghorne & O'Connell 1949, CoU man 1962, Persson & Thilander 1968a, O'Neil 1975, Haugen et al 1977; in vivo, it has been noted that plaque composition is definitely altered, presumably as a result of selective inhibition (Coppes et al-1967, Heaney et al 1972. Pihlstrom et al (1977) considered that the total number of microorganisms was not noticeably reduced by eugenol.…”
Section: Therapeutic Effectsmentioning
confidence: 99%
“…The incorporation of bactericidal or bacteriostatic agents in dressings has been of limited clinical value (Sachs et al 1984, Newman 1986. O'Neil (1975) reported the varied antimicrobial effect of five different dressings in vitro, and Haugen et al (1977) demonstrated a decrease in antibacterial activity of dressings with time. Bay & Langebaek (1978) showed no enhanced plaque inhibition with chlorhexidine impregnated dressings.…”
mentioning
confidence: 99%
“…The prophylactic effect of local or systemic antibiotic delivery may overlap the therapeutic outcomes of periodontal dressing as observed in the treatment modalities of two of the included articles . In other words, periodontal dressings simply act as a physical barrier . Future studies should contain larger sample size, longer follow‐up and better control to verify the observations noted in this paper.…”
Section: Discussionmentioning
confidence: 99%